Pengaruh Edukasi Kesehatan Terhadap Peningkatan Pengetahuan Bahaya Fast Food pada Siswa SMAN 21 Medan - Aiga Nurkhalilah Pasaribu; Aidha, Zuhrina; Tanjung, Nadya Ulfa (LPPM Hang Tuah Pekanbaru, 2024)
Fast food is food that is served in a short time. The habit of consuming fast food excessively will cause many health problems such as obesity commonly called overweight. The behavior of consuming fast food greatly affects a person's knowledge. Therefore, this researcher conducts health education to increase students' knowledge of the dangers of fast food. This study aims to determine the influence of health education on the level of knowledge of the dangers of fast food in adolescents, especially in students of SMAN 21 Medan. The method in this study is quantitative with an experimental approach. The population in this study is 586 students in grades 10 and 11 at SMAN 21 Medan, with a sample of 238 students. This research was carried out by providing pre-test questionnaires and education and then giving time for a week to do a post-test to see the increase in the knowledge of students before and after education. By using univariate and also bivariate analysis. This study obtained results, namely the frequency of male students as many as 79 people, and female students as many as 159 people. In the One Sample Kolmogrov-Smirmov Test, the average or mean in the pre-test was 14.9790, and the average or mean in the post-test was 18.3151. Where from these results it was found that the average increase was 3.3361. From the results of this study, it can be concluded that there is an influence of education on increasing knowledge about the dangers of fast food in SMAN 21 Medan students.